2021
DOI: 10.1093/scan/nsab097
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a counter-empathy processing model: evidence from functional magnetic resonance imaging

Abstract: Counter-empathy significantly affects people’s social lives. Previous evidence indicates that the degree of counter-empathy can be either strong or weak. Strong counter-empathy easily occurs when empathizers are prejudiced against the targets of empathy (e.g. prejudice against outgroup members) and activates brain regions that are opposite to those activated by empathy. Weak counter-empathy may have different neural processing paths from strong ones, but its underlying neural mechanisms remain unclear. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Counter-empathy easily occurs when people are prejudiced against others. 23 Due to the lack of familiarity with strangers and a bad impression of persons who had bad relationships with them; after a transgression, people tend to be prejudiced against them and perceive them as “bad men.” Thus, people tend to show increased counter-empathy for the “bad guys” after the transgression. However, after the transgression, they only feel decreased empathy for “good men” (ie, their friends) whose misfortunes are not deserved, rather than counter-empathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Counter-empathy easily occurs when people are prejudiced against others. 23 Due to the lack of familiarity with strangers and a bad impression of persons who had bad relationships with them; after a transgression, people tend to be prejudiced against them and perceive them as “bad men.” Thus, people tend to show increased counter-empathy for the “bad guys” after the transgression. However, after the transgression, they only feel decreased empathy for “good men” (ie, their friends) whose misfortunes are not deserved, rather than counter-empathy.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that counter-empathy requires more cognitive processing than empathy. 23 It means that people may suffer more cognitive stress after being offended by strangers or persons with whom they had bad relationships, compared to being offended by intimate friends. This should be taken seriously by psychological workers in the clinical and counseling fields.…”
Section: Discussionmentioning
confidence: 99%
“…Another study 5 , investigating the functional correlated of empathy using functional MRI (fMRI), found activations in the middle temporal gyrus and inferior frontal gyri when respondents had to make empathic judgments in a verbal task. More recently, Jie et al 25 showed that both empathy and counter-empathy, which refers to emotional reactions that are incongruent (or even at odds with the emotional states of others) shared a common neural mechanism in the middle temporal gyrus.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, screening for counter-empathy characteristics is of great significance for psychological research. A measurement tool for trait counter-empathy would allow the easy identification of people prone to counter-empathy toward others, with theoretical and practical significance (Jie et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Previous evidence indicates that the degree of counter-empathy can be either strong or weak (Jie et al, 2022). Broadly speaking, counter-empathy refers to emotional reactions that are incongruent, or even at odds, with the emotional states of others (Yamada et al, 2011).…”
Section: Introductionmentioning
confidence: 99%